2019
DOI: 10.1111/ppl.13043
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variations in salicylic acid and hydrogen peroxide in sunflower seeds during transition from dormancy to germination

Abstract: Phytohormones and reactive oxygen species mediate processes such as germination and dormancy. The elucidation of the physiological and biochemical events implicated in the transition from dormancy to germination in different plant species such as sunflower becomes a topic of interest. In this study, we investigated the spatiotemporal variation of salicylic acid (SA), hydrogen peroxide (H 2 O 2 ) and the activity of two antioxidant enzymes (catalase, CAT -EC 1.11.1.6 and ascorbate peroxidase -EC 1.11.1.11) in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…ROS accumulate in seeds upon AR and dormancy release and promote germination in several species, as illustrated by studies in A. thaliana, Pisum sativum, Helianthus annuus, Hordeum vulgare, and Triticum aestivum [40,[45][46][47][48]. In A. thaliana and H. annuus AR seeds, while ROS are localized close to the radicle tip of the embryonic axis during imbibition, they do not have a particular distribution in dormant embryos [49][50][51]. It is widely known that ROS act as signalling molecules, but H 2 O 2 seems to be the main responsible for redox signalling, probably because of its stability.…”
Section: Ros Affect Dormancy Releasementioning
confidence: 99%
“…ROS accumulate in seeds upon AR and dormancy release and promote germination in several species, as illustrated by studies in A. thaliana, Pisum sativum, Helianthus annuus, Hordeum vulgare, and Triticum aestivum [40,[45][46][47][48]. In A. thaliana and H. annuus AR seeds, while ROS are localized close to the radicle tip of the embryonic axis during imbibition, they do not have a particular distribution in dormant embryos [49][50][51]. It is widely known that ROS act as signalling molecules, but H 2 O 2 seems to be the main responsible for redox signalling, probably because of its stability.…”
Section: Ros Affect Dormancy Releasementioning
confidence: 99%
“…Previous studies have reported that ABA accumulates during seed development and this in turn leads to the establishment and maintenance of seed dormancy, which is related to inhibition of early germination (Finkelstein, 2010; Shu et al., 2016). Even more, in species such as A. thaliana (L.) Heynh or sunflower, seed dormancy correlates with high ABA levels (Iwasaki et al., 2022; Vigliocco et al., 2019). In agreement with these previous findings, in our study the dormant line Xi3 had higher levels of ABA in the embryo (embryonic axis + cotyledons) than X274, especially in the embryonic axis, which has been proposed as the center where the occurrence of germination is “decided” (Tophan et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because ROS could play a role in regulating seed germination by oxidizing the proteins that trigger germination (El-Maarouf-Bouteau et al, 2013) and weakening the endosperm during seed swelling (Müller et al, 2009). In a recent report, the dormancy release was associated with increasing the sunflower seeds' internal H 2 O 2 level (Vigliocco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%